Escapes from Russian Captivity by Prisoners of War Taken on the Eastern Front (August 1914 – February 1917). Issue 2 (3rd April 2021) - Miodowski, Adam
ABSTRACT: During the Great War, more than 2 million prisoners from the armies of the Central Powers found themselves in Russian captivity. Most of those soldiers were captured between 1914 and 1916. Apart from the wounded and those taken prisoner in combat, the group of POWs also included deserters and those who had consciously decided to surrender to the Russians on the battlefield. Initially, Russian military authorities attempted to establish POW camps far from large cities and railway lines. However, the growing number of prisoners and the shortage of the financial resources necessary for the construction of new camps forced a change in the original plans. Therefore, new groups of prisoners were directed to cities to be accommodated in existing buildings, hastily adapted for their needs. These circumstances were conducive to escapes. However, getting out of Siberia or Central Asia was not easy. Consequently, the percentage of those who made that effort, in relation to the overall number of prisoners of war kept on the far side of the Urals, was low. According to official Russian data, only several hundred POWs escaped from their camps every month. Of those, only few would reach Sweden, Persia, or China. It was only the Treaty of Brest-Litovsk in March 1918 that allowed the mass of 2 million prisoners to be repatriated from Russia. The scholarly research initiated anew by historians on the centenary of the end of the Great War should take a broader account of the subject matter of prisoners of war, particularly with regard to those captured on the Eastern and Caucasian Fronts. The present article seeks to address this need.